Efek Pengembangan Karir dan Kompetensi pada Kinerja Karyawan Gen Z di PT Securindo Packatama Indonesia - Halimatussa’diah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the effect of career development and competence on the performance of Generation Z employees at PT. Securindo Packatama Indonesia. The research background highlights the importance of human resource management in addressing the challenges of a new workforce generation, which differs from previous ones in terms of career orientation, technological adaptability, and work flexibility. A quantitative approach was employed, using a survey method through questionnaires distributed to Gen Z employees across various divisions of the company. Data were analyzed using multiple linear regression to examine both simultaneous and partial effects of career development and competence variables on employee performance. The results reveal that career development has a positive and significant effect on the performance of Gen Z employees. Likewise, competence shows a significant positive impact in enhancing work quality, productivity, and goal achievement. Simultaneously, these two variables strongly contribute to explaining the variation in employee performance. The findings emphasize the importance of organizational strategies in designing clear career development programs and continuous competency enhancement to support the optimal performance of the new generation workforce.